Sensor Fusion for Operational Mode Shape Analysis of Multi DoF Systems. (2018) - Rahul, R.; Rajpal, Rohit; Aditya Raman Kuchibhatla, Sai; Gangadharan, K.V.
Abstract: This paper presents an experimental approach to study the dynamic behavior of a multi DOF system by sensor fusion technique. An experimental model is designed and developed to simulate real dynamic problem. Frequency response function (FRF) is obtained by conducting impact hammer test from which natural frequencies of the system are identified. Mode shapes are analyzed using forced vibration test at selected frequency zones. This study illustrates the benefits of using sensor fusion for the study of behavior of complex dynamic systems.